2005
DOI: 10.1149/1.2104067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrate on the Repassivation Potential of Alloy 22 in Chloride-Containing Environments

Abstract: The study of Alloy 22 was undertaken in several selected nitrate/chloride (NO 3-/Cl-) electrolytes with chloride concentrations [Cl-] of 1.0, 3.5 and 6.0 molal with [NO 3-]/[Cl-] ratios of 0.05, 0.15 and 0.5 at temperatures up to 100 o C. Results showed that the repassivation potentials increased with increase in [NO 3-]/[Cl-] ratio and decreased with increase in temperature. The absolute [Cl-] was found to have less of an effect on the repassivation potential compared with temperature and the NO 3-/Cl-. Regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 29 publications
1
52
0
Order By: Relevance
“…Brossia andKelly 1998, Ilevbare et al 2005]. This has been demonstrated for Alloy 22 in the temperature range 60 to 100°C for aqueous solutions of 1, 3.5 and 6 molal Cl [Ilevbare et al 2005]. In the Ilevbare et al study, localized corrosion inhibition was observed at 60°C with nitrate to chloride ratio of 0.15 and at 100°C with a ratio of 0.5…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Brossia andKelly 1998, Ilevbare et al 2005]. This has been demonstrated for Alloy 22 in the temperature range 60 to 100°C for aqueous solutions of 1, 3.5 and 6 molal Cl [Ilevbare et al 2005]. In the Ilevbare et al study, localized corrosion inhibition was observed at 60°C with nitrate to chloride ratio of 0.15 and at 100°C with a ratio of 0.5…”
Section: Introductionmentioning
confidence: 90%
“…LLNL has shown that nitrate is an effective inhibitor of chloride induced localized corrosion of Alloy 22 in the temperature range 60 -100°C and for concentrations of 1, 3.5 and 6 molal Cl [Ilevbare et al 2005]. Localized corrosion inhibition was observed at 60°C with nitrate to chloride ratio of 0.15 and at 100°C with a ratio of 0.5.…”
Section: Corrosionmentioning
confidence: 98%
“…13 Before mounting them onto the metallic specimens, the CF were covered with PTFE tape to ensure a tight crevicing gap. [14][15][16] The specimens had a ground finish of 600grit paper. There are two types of specimens mentioned in this work: (1) The as-received wrought mill annealed (MA) and (2) the solution heat-treated (MA + SHT) which were annealed in air for 20 min at 1121°C and then water quenched.…”
Section: Methodsmentioning
confidence: 99%
“…2 The common acceptance criterion for the maximum allowed corrosion rate for Alloy 22 is 80 mpy or 2 mm/year. 15 After the corrosion immersion tests each specimen was thoroughly inspected under optical microscopy (stereomicroscope). Results are given in Table 2.3.…”
Section: +mentioning
confidence: 99%
“…'-I2 It has been reported that Alloy 22 may suffer localized corrosion such as crevice corrosion when it is is also known that the presence of nitrate (NO3-) and other oxyanions in the solution minimizes or eliminates the susceptibility of Alloy 22 to crevice corrosion. 84031G- 23 The value of the ratio ([NO,-]/([Cl-]) has a strong effect of the susceptibility of Alloy 22 to crevice corrosion.…”
Section: Introductionmentioning
confidence: 99%